Effects of Renal Sympathetic Denervation on 24-hour Blood Pressure Variability - Zuern, Christine S.; Rizas, Konstantinos D.; Eick, Christian; Stoleriu, Cosmina; Bunk, Lena; Barthel, Petra; Balletshofer, Bernd; Gawaz, Meinrad; Bauer, Axel (Frontiers in Physiology, 2012)
Background: In patients with arterial hypertension, increased blood pressure (BP) variability contributes to end organ damage independently from mean levels of arterial BP. Increased BP variability has been linked to alterations in autonomic function including sympathetic overdrive. We hypothesized that catheter-based renal sympathetic denervation (RDN) confers beneficial effects on BP variability. Methods and Results: Eleven consecutive patients with therapy-refractory arterial hypertension (age 68.9 ± 7.0 years; baseline systolic BP 189 ± 23 mmHg despite medication with 5.6 ± 2.1 antihypertensive drugs) underwent bilateral RDN. Twenty-four hour ambulatory BP monitoring (ABPM) was performed before RDN and 6 months thereafter. BP variability was primarily assessed by means of standard deviation of 24-h systolic arterial BP (SDsys). Secondary measures of BP variability were maximum systolic BP (MAXsys) and maximum difference between two consecutive readings of systolic BP (Δmaxsys) over 24 h. Six months after RDN, SDsys, MAXsys, and Δmaxsys were significantly reduced from 16.9 ± 4.6 to 13.5 ± 2.5 mmHg (p = 0.003), from 190 ± 22 to 172 ± 20 mmHg (p < 0.001), and from 40 ± 15 to 28 ± 7 mmHg (p = 0.006), respectively, without changes in concomitant antihypertensive therapy. Reductions of SDsys, MAXsys, and Δmaxsys were observed in 10/11 (90.9%), 11/11 (100%), and 9/11 (81.8%) patients, respectively. Although we noted a significant reduction of systolic office BP by 30.4 ± 27.7 mmHg (p = 0.007), there was only a trend in reduction of average systolic BP assessed from ABPM (149 ± 19 to 142 ± 18 mmHg; p = 0.086). Conclusion: In patients with therapy-refractory arterial hypertension, RDN leads to significant reductions of BP variability. Effects of RDN on BP variability over 24 h were more pronounced than on average levels of BP.